Legal Protection System for Children Left Behind by Indonesian Migrant Workers: A Multilevel SCII Strategy Approach - Maemunah, Maemunah; Rejeki, Sri; Syahrial Haq, Hilman; Sakban, Abdul (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
This study investigates the systemic neglect experienced by children of Indonesian migrant workers through the lens of the SCII (Societal, Community, Institutional, Individual) strategy. Despite the economic benefits of labor migration, an estimated 11,732 children in East Lombok remain in vulnerable caregiving arrangements, often overseen by elderly or extended family members. Using an empirical juridical method, data were collected from March to July 2025 through semi-structured interviews, field observations, and document analyses involving seven key informants, including government officials, caregivers, and child protection advocates. The findings reveal a 70% gap between national child protection mandates and local enforcement. For example, only two of ten migrant-sending villages possess local regulations addressing the welfare of left-behind children. Cultural norms such as begawé (communal work) and saling jaga (mutual care) create informal safety nets but also obscure neglect and discourage reporting due to respect for kinship hierarchies. Institutional actors such as schools and health centers remain underutilized; 80% of teachers interviewed lacked standard procedures to identify or report neglect cases. The study highlights SCII’s potential to integrate formal legal mandates with community-based practices and concludes that a pluralistic, multilevel, and context-sensitive protection model is essential to ensure accountability and sustainability in safeguarding migrant workers’ children.